Kontekstualisasi Konsep Keselamatan Manusia dalam Injil Bagi Penganut Kepercayaan Aluk To Dolo - Novianti, Delpi; Nainggolan, Alon Mandimpu; Tumba, Patresia Rante (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2023)
The Gospel of salvation must be conveyed to all people so that they believe and accept Jesus as the only savior. To carry out this mission, a contextual way of theology is needed, including using the culture of the prospective recipient of the Gospel. Within the Toraja community in the province of South Sulawesi, some still adhere to the Aluk To Dolo belief. They have a mythology about creation and humanity's fall into sin, similar to similar stories in the Bible. This research wants to know whether this mythology can be a medium to preach the Gospel of salvation in Jesus Christ to Aluk To Dolo adherents. The research method used is a literature study. The data is taken from various literature; mainly the research results on the mythology of Aluk To Dolo. The research results obtained from a comparison between the Aluk To Dolo mythology and the Bible story about the creation and fall of humans show that the human intermediary with God in the Aluk To Dolo mythology failed to save humans, but Jesus succeeded. Therefore, Jesus is the only savior for humanity. Everyone who believes in Jesus will return to God. Thus, the Aluk To Dolo mythology about the creation and fall of humans into sin can be an effective medium for preaching the Gospel of salvation to Aluk To Dolo adherents.